TRENDS OF SECONDARY EDUCATION DEVELOPMENT IN THE USA, GREAT BRITAIN AND UKRAINE THROUGH REFORMS and INNOVATIONS - Mary Tymenko (National Academy of Educational Sciences of Ukraine, 2019)
In this article, the author discovers some aspects of the transformations of secondary education in the United States and Great Britain through the prism of innovations and reforms. In the article, the generalized classification of the educational reforms (additional reforms, external reforms, regulatory reforms structural reforms) is presented. Based on the findings of the well-known American and British scholars on the problem of secondary education development the author highlighted their conclusions about the efficiency of the educational reforms. The paper highlights the link between innovations and reforms in secondary education in the USA and British education systems. The author highlited the view of the European Union on the role of key competencies for innovative education, development of a personality. The conclusion is made that the idea of key competences in Europe is synchronysed with the idea of basic/life skills in USA and in the world. The author analyses the essence of the transformational processes taking place in the Ukrainian school education, in particular, the implementation of the school reform "New Ukrainian School". The author characterises the "New Ukrainian School" concept that comprises the following basic ideas, i.e. new content of education, based on key competencies necessary for successful self-realization of a child in the society; pedagogy, based on a partnership between a student, a teacher and parents;motivated teacher who has the freedom of creativity and develops professionally;orientation to the needs of a student in the educational process; values-oriented education; a new school structure allowing students to master the new content well and gain key competence for life;decentralisation and effective management providing real autonomy of a school. In the article, the list of key competencies identified by the Ukrainian legislation as basic for the development of a successful personality is characterised.